(untitled) (Research, Society and Development, 2021)
When we refer to Agroecology, we are focusing on a set of principles (unit) and, when we refer to Ecological Agriculture, we refer to concrete manifestations or the materialization of these concepts (diversity), through specific forms of management. This set of initiatives / experiences, in a holistic view, which considers the complexity and the relationship between the various processes that occur in agroecosystems, configures an agricultural model based on ecological principles of production, which is opposed to modern agriculture. This article aimed to carry out a bibliographical survey on the main ecologically-based production systems, with an emphasis on the organic system. Using previously selected descriptors, an active search was carried out in the main research platforms, for articles, dissertations and theses that addressed as main or secondary theme the main forms of ecological agriculture: Biodynamic, Natural, Biological and Organic. Far beyond the absence of the use of pesticides, adherence to ecologically-based agriculture, more specifically, to organic-based agriculture, is expansive and involves social, environmental and economic issues. In addition to intrinsically defending the right to life and health, of producers and consumers, ecological agriculture involves the practice of solidarity economy, valuing small farmers and contributing to their independence, in addition to bringing important points such as sustainability, preservation of the environment, respect for local knowledge and not wasting food and resources.